Genetische Diagnostik bei Kardiomyopathien - Czepluch, Frauke; Wollnik, Bernd; Hasenfuß, Gerd (DMW - Deutsche Medizinische Wochenschrift, 2017)
Cardiomyopathies often have a genetic etiology. New genetic diagnostic strategies based on next generation sequencing (NGS)-approaches will continuously increase our knowledge about the genetic basis of cardiomyopathies within the following years. Diagnostics and therapy of rare, genetically-induced cardiac diseases increasingly require special cardiac and genetic knowledge. Interestingly, mutations in the same gene or even identical gene mutations can be associated with different cardiomyopathy phenotypes and can exhibit incomplete penetrance or variable expressivity. In the future, the correct interpretation and classification of novel gene variants identified in patients with inherited cardiomyopathy forms will represent a great challenge. Genetic counselling and – if appropriate – subsequent genetic testing for cardiomyopathy patients and their asymptomatic relatives is essential for an early diagnosis of the disease, a prognostic evaluation and possibly for the start of preventive or therapeutic measures.
Keywords: Kardiomyopathie; DCM; HCM; Genetische Testung; Kardiogenetik